Inhaled corticosteroids and bone density of children with asthma - (:unkn) unknown (My University, 2002)
In this cross-sectional study, we aimed to compare anteroposterior (AP) spine and total body bone mineral density (BMD) measurements of children with asthma treated with long-term inhaled budesonide (n = 52, mean age 6.4+/-2.2yr, M/F = 22/30) (Group I) with those of asthmatic children who had never received treatment with inhaled corticosteroids (Group II) (n = 22, mean age 6.8+/-2.2, M/F = 10/12). Boys and girls were comparable for age, weight, height, cumulative corticosteroid (CS) dosage, duration of disease and inhaled corticosteroid (ICS) treatment within each group. The mean total accumulated dosage of budesonide for children in Group I was 154.0+/-135.3mg (mean daily dosage = 419+/-154 microg) and the mean treatment duration was 13.0+/-9.8 months. The two groups were comparable with respect to age, gender, weight, height, Tanner's stage and duration of disease. There was no significant difference between subjects in the two groups for total (p = 0.214) and (AP) spine BMD results (p = 0.661), respectively. Our results provide additional support for the safety of ICS therapy on bone density of asthmatic children.
Keywords: Female; Humans; Cross-Sectional Studies; Male; Child; Child, Preschool; Dose-Response Relationship, Drug; Anti-Inflammatory Agents; Administration, Inhalation; Asthma; Budesonide; Spine; Bone Density; Safety